Efektifitas Yurisdiksi Cybercrime Di Tengah Perkembangan Teknologi Informasi - Amanda Fitria Najwa; Aqila Husna (International Forum of Researchers and Lecturers, 2024)
This journal discusses the influence of the development of information technology which cannot be separated from the existence of jurisdiction, which jurisdiction is effective or not in its implementation, so it must be discussed how this jurisdiction can be effective in its implementation, the existence of the ITE Law can pave the way for law enforcement in cyber crime because in the ITE Law, sanctions can be applied to both Indonesian citizens themselves and foreign citizens who commit cyber crime and harm the Indonesian state, however, to carry out legal actions with foreign actors, it must be ensured that the country also has regulations regarding cybercrime, and the ratification of Indonesia's ability to apply for the extradition of perpetrators will be stronger.